BLUE CAP MOVEMENT® - Selvalingam, S.; Azad Hassan, A.R.; Lim, J. (University of Malaya, 2015)
The Blue Cap Movement was initiated by urologists from the Faculty of Medicine, University of Malaya and prostate cancer survivors from the Prostate Cancer Support Group. It was founded in June 2015 with the motto \'Blue in Cap but Pink in Health\'. Our main partner is Malaysian Health Promotion Board (MySihat) under the Ministry of Health. This non-profit movement is supported by the University of Malaya, Malaysian Urology Foundation and Malaysian Urological Association (www.muacme.org). Our main focus areas the following; - i. To create awareness amongst the public on Men\'s Health and urological cancers (Prostate Cancer, Bladder Cancer, Kidney Cancer, Testicular Cancer and Penile Cancer). ii. To promote a normal and healthy lifestyle after cancer treatment. iii. To encourage cancer patients to exercise by promoting Exercise Support Groups. iv. To promote healthy lifestyle amongst Malaysian in prevention of cancer. v. To encourage students and youth participation in creating awareness of Men\'s Health. vi. To raise funds in support of the Blue Cap Movement programs. All funds received through the activities of this movement will be channeled to the \'Urological Cancer Trust Fund\' set up under the Bursary, University of Malaya. The management of this trust fund will be governed by a board of 9 members consisting of urologists and members of the public. The trust fund will be used for the following purposes: i. Financial assistance to Malaysian patients with urological cancer, especially prostate cancer patients who can\'t afford the recommended treatment. ii. Education and training for urological cancer treatment and awareness programs in Malaysia. iii. Urological cancer research in Malaysia. iv. Community directed activities of the Prostate Cancer Support Group and Blue Cap Movement towards promoting Men\'s Health. v. Any other expenditures as deemed appropriate and approved by the Board members. The trademark registered in class 25, 35, 36, 41, 42, 44 and 45.